"Thank you for letting it be about me": Women's perceptions of holistic programming in a jail. Issue 4 (19th May 2017) - Praetorius, Regina; Frank Terry, Laura; Burse, Jacqueline
ABSTRACT: Incarcerated women often have trauma, substance misuse, and mental health concerns. These are often categorized as criminal activity. While data suggest women are incarcerated largely due to substance related issues, there is a gap in jail services. Women are often revictimized in jails, creating additional rehabilitation barriers. There is demand for programming to address substance misuse, mental health, life skills, and community building. This study's purpose was to understand perceptions of holistic jail programming. Participants' journals were analyzed ( n = 132). Themes included intentionality, process feelings, self-worth, solidarity, programming justification, and emotional safety. The programming has promising elements to be replicated.